Factors associated with outcomes in surgically managed ruptured cerebral aneurysms - Chee, Lai Chuang (2017)
Background: Ruptured cerebral aneurysm is a life-threatening condition that requires urgent medical attention. In Malaysia, a prospective study by Hospital Sarawak Neurosurgical center in year 2000-2002 revealed an average of 2 cases of intracranial aneurysm per month with an operative mortality of 20% and management mortality of 25%. Failure to recognize, delay in admission to neurosurgical center and lack of facilities may lead to poor surgical outcome of these patients. The purpose of the study is to review the epidemiology of the ruptured cerebral aneurysm who underwent surgical clipping in this region and to identify the predicting factors that influence the prognosis and outcome of these patients. Material and method: A single center retrospective study with review of medical records was performed involving 105 patients who were surgically treated for ruptured intracranial aneurysm in Hospital Sultanah Aminah, Johor Bahru from July 2011 until January 2016. Information collected including the patient’s demographics data, Glasgow Coma Scale (GCS) prior to surgery, World Federation of Neurosurgical Societies Scale (WFNS) of the patients and timing between SAH ictus and surgery. Good clinical grade is defined as WFNS grade I-III while poor grade as WFNS grade IV and V. The outcomes at discharge and after 6th months of surgery were assessed using modified Rankin’s Scale (mRS). mRS scores of 0 to 2 were grouped into “favourable” and mRS scores of 3 to 6 were grouped into “unfavourable”. Only cases of proven ruptured aneurysmal SAH involving anterior circulation and underwent surgical clipping were included in the study. Data collected were analyzed using SPSS. Univariate and multivariate analysis were performed and p value of < 0.05 was taken as statistical significance. Result: A total of 105 patients were included which consisted of 42.9% male and 57.1% of female patients. The mean GCS of the patient subjected for surgical clipping was 13 with majority fall into the good clinical grade (78.1%). Mean timing of surgery after SAH was 5.3 days and was further categorized into early (day 1 to day 3, 45.3%), intermediate (day 4-day 10, 56.2%) and late (after day 10, 9.5%). Total favourable outcome achieved` at discharge was 59.0% as compare to 41.0% of unfavourable outcome with an overall mortality rate of 10.5%. At 6th month of review (n=94), the patient with favourable outcome constituted 71.3% as compared to 28.7% with unfavourable outcome. The mortality at 6th month was 3.2%. On univariate analysis, early surgical clipping, patient with better GCS and good clinical grade had significant better outcome at discharge. Timing of surgery and clinical grade remained significant predictors for outcome at 6th month base on univariate study. On multivariate analysis, younger age male patient with good clinical grade is associated with favourable outcome at discharge when other factors were adjusted. Multivariate analysis done for outcome at 6th month showed only male patient and good clinical grade was associated with favourable outcome. Conclusion: In our study, we conclude that younger male patient with good clinical grade are associated with favorable outcome at discharge and at 6th month post-surgery. We do not find timing of surgery, size of aneurysm and duration of surgery to be associated with the outcome of the patient post clipping. Increasing age is not associated with surgical outcome in longer term of patient’s follow up.